Fixed Point Results via G-Function over the Complete Partial b-Metric Space. (12th December 2020) - Alzaid, Sara Salem; Fulga, Andreea; Alqahtani, Badr
Abstract : In this paper, we consider an auxiliary function G to combine and unify several existing fixed point theorems in the setting of the complete partial b -metric space. We consider also some examples to support the observed main results.